Developmental validation of the ParaDNA® Body Fluid ID System. (December 2017) - Blackman, S.; Stafford-Allen, B.; Hanson, E.; Panasiuk, M.; Brooker, A.; Rendell, P.; Ballantyne, J.; Wells, S.
Abstract: LGC has developed a rapid mRNA-based body fluid test that runs on the ParaDNA ® System, a direct sampling and instrument platform utilizing HyBeacon ® hybridization probes and end-point melt detection. The ParaDNA Body Fluid ID Test can detect and identify six different body fluids; vaginal fluid, seminal fluid, sperm cells, saliva, menstrual blood and peripheral blood. Crime stains or swabs are directly sampled to collect a small percentage of material from the item for delivery into pre-prepared chemistry within each test plate. Here we describe some of the ParaDNA Body Fluid ID Test developmental validation studies. The validation assessed performance of the different body fluid markers in the test, including sensitivity, sample aging/environmental studies, mixtures and exposure to various inhibitors.